2010
DOI: 10.3109/08037050903516284
|View full text |Cite
|
Sign up to set email alerts
|

The mean platelet volume in patients with non-dipper hypertension compared to dippers and normotensives

Abstract: Our results suggest that MPV, a determinant of platelet activation, has a positively correlation with blood pressure and elevated in non-dipper compared with dippers and controls. Increased platelet activation could contribute to increase the atherosclerotic risk in non-dipper patients compared with dippers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 26 publications
1
31
3
2
Order By: Relevance
“…Contrary to most previous studies, (3)(4)(5)(6)(7)(8) factors in atherogenesis and also in CV risk prediction. Namely, the FRS does not account for metabolic syndrome which is strongly associated with atherogenesis, and often underestimates total CV risk in patients with these risk factors.…”
Section: Discussioncontrasting
confidence: 70%
“…Contrary to most previous studies, (3)(4)(5)(6)(7)(8) factors in atherogenesis and also in CV risk prediction. Namely, the FRS does not account for metabolic syndrome which is strongly associated with atherogenesis, and often underestimates total CV risk in patients with these risk factors.…”
Section: Discussioncontrasting
confidence: 70%
“…Nocturnal decline in BP is a physiological condition [18]. Subjects in whom this nocturnal reduction in BP is blunted are named non-dippers whereas the others are classified as dippers [4,5,6,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous studies have found elevated MPV values in resistant hypertension 6 and non-dipper hypertension. 7 However, whether an elevated MPV can independently predict future risk for hypertension has not been noted in the literature. In the present study, we evaluated whether elevated MPV could independently predict future risk for hypertension.…”
Section: Introductionmentioning
confidence: 99%